Psychological impact of infertility among infertile women - Hasanpoor Azghdy, Syede Batool; simbar, Masoumeh; Vedadhir, Abouali; Hossein Rashid, Batool (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Infertility is a important life event which it and its treatment can affect lives of couples. Infertility can cause various psychological-emotional disorders or consequences. The aim of this study was to explore psychological experiences of infertility and its treatment in infertile women attending to Vali-e-Asr Fertility Health Research Center Tehran,Iran. Methods: This qualitative study was carried out on 15 women with primary and secondary infertilityThe study was conducted in Vali-e-Asr Fertility Health Research Center in Tehran. A judgemental method was used to recruit participants in the study. Data were collected using semi-structured interviews and continued until data saturation. Simultaneously in process of data collection, the data analysis phase was performed with conventional content analysis method. Findings: main concepts emerged from the data were categorized into four main themes and their sub-categories include: 1. Cognitive reactions of infertility 2. Cognitive reactions to therapy process 3. Emotional–affective reactions of infertility 4. Emotional–affective reactions to therapy process. Conclusion: This study showed that the infertility and its treatment process for Iranian infertile women is a source of psychological suffering with devastating effects on psychological well-being of infertile couples. The results also showed that one of the major causes of psychological distress is the social pressure by community members, while is less attention is paid to the sociocultural dimensions and consequences of infertility. Keywords: infertility; psychological; seeking treatment; content analysis REFERENCES Berek JS (2007). Berek & Novak’s Gynecology . 14th edition. Lippincott Williams and Wilkins, Philadelphia. Bliss C (1999). The Social Construction of Infertility by Minority Women . (Dissertation). Available at: http:// gerrystahl.net/personal/family/dissertation.pdf/.Accessed Nov 5, 2012. Cousineau TM, Domar AD (2007). Psychological impact of infertility. Best Practice & Research Clinical Obstetrics & Gynaecology . 21(2) 293- 308. Cwikel J, Gidron Y, Sheiner E (2004). "Psychological interactions with infertility among women: Review". European Journal of Obstetrics & Gynecology and Reproductive Biology . 117(2) 126-31. Domar AD, Gordon K (2011)."The Psychological Impact of Infertility: Results of a national survey of men and women". Fertility and Sterility . 95(4)S17. Dyer SJ (2009). "Psychological and social aspects of infertility in developing countries". International Journal of Gynecology & Obstetrics . 107 (Supplement 2):S25-S26. Dyer SJ et al (2002). "Men leave me as I can not have childern: women’s experiences with involuntary childlessness". Human Reproduction . 17 (6)1663-1668. Gameiro S et al (2012). "Why do patients discontinue fertility treatment? A systematic review of reasons and predictors of discontinuation in fertility treatment". Human Reproduction Update .18(6) 652- 669. Gannon K, Glover L, Abel P (2004). "Masculinity, infertility, Stigma and media reports". Social Science & Medicine . 59(6) 1169-75. Greil AL, Blevins KS, McQuillan J (2010). "The experience of infertility: A review of recent literature". Sociology of Health & Illness . 32(1)140–162. Guerra D et al (1998). "Psychiatric morbidity in couples attending a fertility Service". Human Reproduction . 13(6) 1733–1736. Hammerli K, Hansjorg Z, Barth J (2009). "The efficacy of psychological interventions for infertile patients: A meta-analysis examining mental health and pregnancy rate". Human Reprod Update .15(3) 279-295. Hart VA (2002). "Infertility and the role of psychotherapy". Issues in Mental Health Nursing . 23(1) 31- 41. Inhorn MC, Birenbaum-Carmeli D (2008). "Assisted reproductive technologies and culture change". Annual Review of Anthropology . 37: 96-177. Latifnejad R (2008). How religious faiths and spiritual beliefs affect the experiences of infertile women seeking infertility treatments: A feminist grounded theory approach . (Dissertation). Guildford, University of Surrey. 2008. Lechner L, Bolman C, van Dalen A (2007). "Definite involuntary childlessness: Associations between coping, social support and psychological distress". Human Reproduction . 22(1) 288-94. Noorbala A et al(2009)."[Prevalence of psychiatric disorders and types of personality in fertile and infertile women". Journal Reprod Infertil . 9(4) 350-360.(Persion). Polit DF, Beck CT (2006). Essentials of Nursing Research Methods, Appraisal and Utilization . 6th edition. Philadelphia:Lippincott Williams Wilkins. Sami N, Tazeen S.A. "Perceptions and Experiences of Women in Karachi- Pakistan Regarding Secondary Infertility: Results from a Community-Based Qualitative Study". Obstetrics and Gynecology International Volume 2012. [ on line].< http://www.hindawi.com/journals/ogi/2012/108756>. [4 Nov 2012]. Slade P et al (2007). "The relationship between perceived stigma, disclosure patterns, support and distress in new attendees at an infertility clinic". Oxford Journals, Medicine, Human Reproduction . 22(8) 2309-2317. Spannagel C, Gläser-Zikuda M, Schroeder U . "Application of qualitative content analysis in user-program interaction research". Forum Qualitative Social Research .2005, 6(2). [ on line].< http://www.qualitativeresearch. net/index.php/fqs/article/view/469>. [13 Oct 2012]. Vahidi S, Ardalan A, Mohammad K (2009). "Prevalence of primary infertility in the Islamic Republic of Iran in 2004-2005". Asian Pacific Journal of Public Health . 21(3) 287-293. (Persian). Van Balen F, Gerrits T (2001). "Quality of infertility care in poor-resource areas and the introduction of new reproductive technologies". Human Reproduction . 16(2) 215-219. Vayena E, Rowe PJ, Griffin PD . "Current Practices and Controversies in Assisted Reproduction". World Health Organization.[ on line].< http://www.imamu.edu.sa/Scientific _selections/files/DocLib/report.pdf>. Published 2002. [13 Oct, 2012]. Wiersema NJ et al. "Consequences of infertility in developing countries: Results of a questionnaire and interview. Survey in the South of Vietnam". Journal of Translational Medicine . Published online 2006; 4: 54. [ on line]. <http://link.springer.com/article/10.1186%2F1479-5876-4-54#page-1>. [5 Nov 2012]. Wischmann T (2008). "Psychosocial aspects of infertile couples ". Psychosocial Gynakol Geburtsmed Gynakol Endokrinol . 4(3) 194–209. Psychological impact of infertility among infertile women seeking treatment: A qualitative study Syede Batool Hasanpoor–Azghdy 1, Masoumeh Simbar2 , Abouali Vedadhir 3, Batool Hossein Rashid 4 1. PhD Alumni of reproductive health, Department of Reproductive Health and Midwifery, Faculty of nursing and midwifery, Shahid Beheshti University of Medical Science. Tehran, Iran. 2. PhD, Associate professor in Reproductive Health, The Research Center for Safe Motherhood , Department of Reproductive Health and Midwifery, Faculty of nursing and midwifery, Shahid Beheshti Medical Sciences University. Tehran, Iran. 3. PhD, Assistant Professor, Department of Anthropology, Faculty of Social Sciences, University of Tehran, Tehran, Iran. 4. PhD, Associate professor in Obstetrician & Gynecologist , Department of Obstetrician & Gynecologist, Valie-Asr Reproductive Health Research Center, Tehran Medical Sciences University. Tehran, Iran. Corresponding author: Masoumeh Simbar; msimabr@ yahoo.com Abstract Background and aim: Infertility is a important life event which it and its treatment can affect lives of couples. Infertility can cause various psychological-emotional disorders or consequences. The aim of this study was to explore psychological experiences of infertility and its treatment in infertile women attending to Vali-e-Asr Fertility Health Research Center Tehran,Iran. Methods: This qualitative study was carried out on 15 women with primary and secondary infertilityThe study was conducted in Vali-e-Asr Fertility Health Research Center in Tehran. A judgemental method was used to recruit participants in the study. Data were collected using semi-structured interviews and continued until data saturation. Simultaneously in process of data collection, the data analysis phase was performed with conventional content analysis method. Findings: main concepts emerged from the data were categorized into four main themes and their sub-categories include: 1. Cognitive reactions of infertility 2. Cognitive reactions to therapy process 3. Emotional–affective reactions of infertility 4. Emotional–affective reactions to therapy process. Conclusion: This study showed that the infertility and its treatment process for Iranian infertile women is a source of psychological suffering with devastating effects on psychological well-being of infertile couples. The results also showed that one of the major causes of psychological distress is the social pressure by community members, while is less attention is paid to the sociocultural dimensions and consequences of infertility. Keywords: infertility; psychological; seeking treatment; content analysis. REFERENCES Berek JS (2007). Berek & Novak’s Gynecology . 14th edition. Lippincott Williams and Wilkins, Philadelphia. Bliss C (1999). The Social Construction of Infertility by Minority Women . (Dissertation). Available at: http:// gerrystahl.net/personal/family/dissertation.pdf/.Accessed Nov 5, 2012. Cousineau TM, Domar AD (2007). Psychological impact of infertility. Best Practice & Research Clinical Obstetrics & Gynaecology . 21(2) 293- 308. Cwikel J, Gidron Y, Sheiner E (2004). "Psychological interactions with infertility among women: Review". European Journal of Obstetrics & Gynecology and Reproductive Biology . 117(2) 126-31. Domar AD, Gordon K (2011)."The Psychological Impact of Infertility: Results of a national survey of men and women". Fertility and Sterility . 95(4)S17. Dyer SJ (2009). "Psychological and social aspects of infertility in developing countries". International Journal of Gynecology & Obstetrics . 107 (Supplement 2):S25-S26. Dyer SJ et al (2002). "Men leave me as I can not have childern: women’s experiences with involuntary childlessness". Human Reproduction . 17 (6)1663-1668. Gameiro S et al (2012). "Why do patients discontinue fertility treatment? A systematic review of reasons and predictors of discontinuation in fertility treatment". Human Reproduction Update .18(6) 652- 669. Gannon K, Glover L, Abel P (2004). "Masculinity, infertility, Stigma and media reports". Social Science & Medicine . 59(6) 1169-75. Greil AL, Blevins KS, McQuillan J (2010). "The experience of infertility: A review of recent literature". Sociology of Health & Illness . 32(1)140–162. Guerra D et al (1998). "Psychiatric morbidity in couples attending a fertility Service". Human Reproduction . 13(6) 1733–1736. Hammerli K, Hansjorg Z, Barth J (2009). "The efficacy of psychological interventions for infertile patients: A meta-analysis examining mental health and pregnancy rate". Human Reprod Update .15(3) 279-295. Hart VA (2002). "Infertility and the role of psychotherapy". Issues in Mental Health Nursing . 23(1) 31- 41. Inhorn MC, Birenbaum-Carmeli D (2008). "Assisted reproductive technologies and culture change". Annual Review of Anthropology . 37: 96-177. Latifnejad R (2008). How religious faiths and spiritual beliefs affect the experiences of infertile women seeking infertility treatments: A feminist grounded theory approach . (Dissertation). Guildford, University of Surrey. 2008. Lechner L, Bolman C, van Dalen A (2007). "Definite involuntary childlessness: Associations between coping, social support and psychological distress". Human Reproduction . 22(1) 288-94. Noorbala A et al(2009)."[Prevalence of psychiatric disorders and types of personality in fertile and infertile women". Journal Reprod Infertil . 9(4) 350-360.(Persion). Polit DF, Beck CT (2006). Essentials of Nursing Research Methods, Appraisal and Utilization . 6th edition. Philadelphia:Lippincott Williams Wilkins. Sami N, Tazeen S.A. "Perceptions and Experiences of Women in Karachi- Pakistan Regarding Secondary Infertility: Results from a Community-Based Qualitative Study". Obstetrics and Gynecology International Volume 2012. [ on line].< http://www.hindawi.com/journals/ogi/2012/108756>. [4 Nov 2012]. Slade P et al (2007). "The relationship between perceived stigma, disclosure patterns, support and distress in new attendees at an infertility clinic". Oxford Journals, Medicine, Human Reproduction . 22(8) 2309-2317. Spannagel C, Gläser-Zikuda M, Schroeder U . "Application of qualitative content analysis in user-program interaction research". Forum Qualitative Social Research .2005, 6(2). [ on line].< http://www.qualitativeresearch. net/index.php/fqs/article/view/469>. [13 Oct 2012]. Vahidi S, Ardalan A, Mohammad K (2009). "Prevalence of primary infertility in the Islamic Republic of Iran in 2004-2005". Asian Pacific Journal of Public Health . 21(3) 287-293. (Persian). Van Balen F, Gerrits T (2001). "Quality of infertility care in poor-resource areas and the introduction of new reproductive technologies". Human Reproduction . 16(2) 215-219. Vayena E, Rowe PJ, Griffin PD . "Current Practices and Controversies in Assisted Reproduction". World Health Organization.[ on line].< http://www.imamu.edu.sa/Scientific _selections/files/DocLib/report.pdf>. Published 2002. [13 Oct, 2012]. Wiersema NJ et al. "Consequences of infertility in developing countries: Results of a questionnaire and interview. Survey in the South of Vietnam". Journal of Translational Medicine . Published online 2006; 4: 54. [ on line]. <http://link.springer.com/article/10.1186%2F1479-5876-4-54#page-1>. [5 Nov 2012]. Wischmann T (2008). "Psychosocial aspects of infertile couples ". Psychosocial Gynakol Geburtsmed Gynakol Endokrinol . 4(3) 194–209.